Building an ensemble using IBM zEnterprise Unified Resource Manager - White, Bill (Telecommunications engineer); Ramos, Elsie; Lascu, Octavian; Ebbers, Mike; Bari, Paola; Dente, Gwen; Fries, Wolfgang; Gašparović, Marian; Hatfield, Brian; McDonough, Jeff; Neville, Iain; Rodolfi, Giancarlo; et al. (IBM redbooks., 2012)
For the first time it is possible to deploy an integrated hardware platform that brings mainframe and distributed technologies together: a system that can start to replace individual islands of computing and that can work to reduce complexity, improve security, and bring applications closer to the data that they need.